Exploring burn first aid knowledge and water lavage practices in Uganda: A cross-sectional study. - Brian Kasagga; Joseph Baruch Baluku; Felix Bongomin; Derrick Kasozi; Eria Muwanguzi; Mercy Namazzi; Yusuf Sadiq; Rose Alenyo; Edris Wamala Kalanzi; Darius Balumuka; Alex Emmanuel Elobu (PLoS ONE)
Background Low- and middle-income countries experience higher burn-related morbidity and mortality compared to high-income countries. Prehospital Burn First Aid (BFA) improves outcomes. We assessed BFA knowledge and water lavage practices and their associated factors among burn victims, caregivers, and visitors at a tertiary health facility in Uganda. Methods A cross-sectional study was conducted at the Burns Unit of Kiruddu National Referral Hospital in Kampala between 1st April 2022 and 30th November 2022. Participants included burn patients, caregivers, and hospital visitors. Data on BFA knowledge and practices were collected using an interviewer-administered questionnaire. BFA knowledge was evaluated using 13 questions, with a ≥80% score considered adequate. Logistic regression was used to assess for associations. Results We enrolled 404 participants, comprising 68 (16.8%) burn victims, 161(39.9%) primary caregivers, and 175 (43.3%) hospital visitors. Overall, 339 (83.9%) participants had never received BFA information, and 392 (97.0%) had no first aid training. The mean BFA knowledge score was 56±13.9%, with only 5.4% of the participants demonstrating adequate knowledge. Only 26 (27.7%) of current and former burn victims used water lavage as BFA. No statistically significant associations were found between BFA knowledge, water lavage usage, and demographic variables at univariable and multivariable binary logistic regression analyses. Conclusion We highlight inadequate BFA knowledge and practices among victims of burns, their caregivers, and the general population. Addressing these deficiencies through community-based initiatives is crucial to improving burn care in Uganda.